Progress in high-temperature plasma research at NCBJ (former IPJ) in Poland - Sadowski, M.J. (Вопросы атомной науки и техники, 2012)
This invited lecture presents the most important results of theoretical and experimental studies of hightemperature plasma, which were performed at the NCBJ (former IPJ) in Otwock-Swierk, Poland, during recent two years. The research activity included: Studies of fast electrons and X-rays in Z-pinch and Tokamak devices; Research on applications of solid-state nuclear track detectors for detection of fast ions and neutrons emitted from plasma in experimental facilities of Z-pinch, Tokamak and ICF type; Investigations of high-temperature plasma streams and their interactions with solid targets; Ultra-high vacuum arc deposition of thin metallic films; Selected studies on plasma engineering of solid surfaces. The formation of the NCBJ (on Sept. 1, 2011) and its successive reorganization (on Jan. 1, 2012) led to the separation of the Division of Plasma Studies (TJ5) which is concentrated on high-temperature plasmas within frames of domestic and international research programs. Представлены наиболее важные результаты теоретического и экспериментального исследований высокотемпературной плазмы, которые были получены в НЦЯИ (бывший ИЯП) в Отвоцк-Шверке, Польша, за последние два года. Исследовательская деятельность включала в себя: исследования быстрых электронов и рентгеновского излучения в устройствах типа Z-пинч и токамаках; исследования по применению твердотельных трековых детекторов для регистрации быстрых ионов и нейтронов, испускаемых плазмой в экспериментальных установках Z-пинч, токамаках и установках инерциального термоядерного синтеза; исследования высокотемпературных плазменных потоков и их взаимодействия с твердыми мишенями; сверхвысокого вакуумно-дугового осаждения тонких металлических пленок; некоторые исследования по плазменной инженерии твердых поверхностей. Образование НЦЯИ (1 сентября 2011) и его последующая реорганизация (1 января 2012) привела к отделению Секции плазменных исследований (TJ5), работа которой направлена на изучение высокотемпературной плазмы в рамках внутренних и международных научно- исследовательских программ. Представлені найбільш важливі результати теоретичного та експериментального дослідження високотемпературної плазми, які були отримані в НЦЯІ (колишній ІЯП) в Отвоцк-Шверк, Польща, за останні два роки. Дослідницька діяльність включала в себе: дослідження швидких електронів і рентгенівського випромінювання в пристроях типу Z-пінч і токамаках; дослідження по застосуванню твердотільних трекових детекторів для реєстрації швидких іонів та нейтронів, що випускаються плазмою в експериментальних установках Z-пінч, токамак і установок інерціального термоядерного синтезу; дослідження високотемпературних плазмових потоків та їх взаємодії з твердими мішенями; надвисокого вакуумно-дугового осадження тонких металевих плівок; деякі дослідження по плазмовій інженерії твердих поверхонь. Утворення НЦЯІ (1 вересня 2011) та його подальша реорганізація (1 січня 2012) призвела до відокремлення Секції плазмових досліджень (TJ5), робота якої спрямована на вивчення високотемпературної плазми в рамках внутрішніх та міжнародних науково-дослідницьких програм.